Metabolic Alterations in the Enoyl-CoA Hydratase 2 Mutant Disrupt Peroxisomal Pathways in Seedlings - Li, Ying (Plant Physiol, 2019)
Mobilization of seed storage compounds, such as starch and oil, is required to provide energy and metabolic building blocks during seedling development. Over 50% of fatty acids in Arabidopsis (Arabidopsis thaliana) seed oil have a cis-double bond on an even-numbered carbon. Degradation of these substrates requires peroxisomal fatty acid β-oxidation plus additional enzyme activities. Such auxiliary enzymes, including the enoyl-CoA hydratase ECH2, convert (R)-3-hydroxyacyl-CoA intermediates to the core β-oxidation substrate (S)-3-hydroxyacyl-CoA. ECH2 was suggested to function in the peroxisomal conversion of indole-3-butyric acid (IBA) to indole-3-acetic acid, because ech2 seedlings have altered IBA responses. The underlying mechanism connecting ECH2 activity and IBA metabolism is unclear. Here, we show that ech2 seedlings have reduced root length, smaller cotyledons, and arrested pavement cell expansion. At the cellular level, reduced oil body mobilization and enlarged peroxisomes suggest compromised β-oxidation. ech2 seedlings accumulate 3-hydroxyoctenoate (C8:1-OH) and 3-hydroxyoctanoate (C8:0-OH), putative hydrolysis products of catabolic intermediates for α-linolenic acid and linoleic acid, respectively. Wild-type seedlings treated with 3-hydroxyoctanoate have ech2-like growth defects and altered IBA responses. ech2 phenotypes are not rescued by Suc or auxin application. However, ech2 phenotypes are suppressed in combination with the core β-oxidation mutants mfp2 or ped1, and ech2 mfp2 seedlings accumulate less C8:1-OH and C8:0-OH than ech2 seedlings. These results indicate that ech2 phenotypes require efficient core β-oxidation. Our findings suggest that low ECH2 activity causes metabolic alterations through a toxic effect of the accumulating intermediates. These effects manifest in altered lipid metabolism and IBA responses leading to disrupted seedling development.